Molecular dynamics simulations of the lattice thermal conductivity of Cu–Ni alloys - Xiao-Ping Wei; Xue Li; Ya-Ling Zhang (AIP Advances, 2025)
It is an inevitable consequence of materials being exposed to elevated levels of particles and heats that they will experience various forms of damage, resulting in changes in their macroscopic properties, including the heat transport characteristics of the material. The effects of temperature, irradiation damage, and tensile strain on the lattice thermal conductivity of Cu–Ni alloys were investigated using the equilibrium molecular dynamics method. The microphysical mechanism of the variation of the lattice thermal conductivity of Cu–Ni alloys is revealed in terms of the density of phonon states, the variation of phase components, and the type, number, and distribution of defects. The results show that the lattice thermal conductivity of Cu–Ni alloys changes with increasing Ni content, which is due to enhanced phonon scattering as a result of poor mass and lattice disorder. The phonon–phonon scattering is exacerbated with increasing temperature, which further leads to a change in the thermal conductivity of the alloys. Compared to pre-irradiation Cu–Ni alloys, the type, quantity, and distribution of defects produced by irradiation will significantly affect the lattice thermal conductivity of Cu–Ni alloys. The tensile strain introduces more phonon scattering centers (e.g., dislocations, grain boundaries, etc.), which further reduces the heat transfer efficiency. This study provides valuable insights into the interplay between alloy composition, understanding of irradiation effects and heat transport properties under mechanical deformation, and contributes to a fundamental understanding of heat transport in disordered metallic systems.